CD36 level and trafficking are determinants of lipolysis in adipocytes - Zhou, Dequan (Federation of American Societies for Experimental Biology, 2012)
CD36 has been linked to the etiology of insulin resistance and inflammation. We explored its function in regulating adipose tissue lipolysis, which influences fat accumulation by liver and muscle and overall metabolism. Knockdown of CD36 in differentiated 3T3-L1 adipocytes decreased lipolysis in response to 10 μM of the β-adrenergic agonist isoproterenol (by 42%), 10 μM of the adenyl cyclase activator forskolin (by 32%), and 500 μM of the phosphodiesterase (PDE) inhibitor isobutylmethylxanthine (by 33%). All three treatments in the knockdown adipocytes were associated with significant decreases of cAMP levels and of the hormone-sensitive lipase (HSL) and perilipin phosphorylation. An important role for PDE was supported by the lack of inhibition of the lipolysis induced by the poorly hydrolyzable dibutyryl cAMP analog. An additional contributory mechanism was diminished activation of the Src-ERK1/2 pathway. Regulation of lipolysis and lipolytic signaling by CD36 was reproduced with adipose tissue from CD36(−/−) mice. The importance of surface CD36 in this regulation was suggested by the finding that the plasma membrane-impermeable CD36 inhibitor sulfo-N-succinimidyl oleate (20 μM) decreased lipolysis. Interestingly, isoproterenol induced CD36 internalization, and this process was blocked by HSL inhibition, suggesting feedback regulation of adipocyte lipolysis via CD36 trafficking.—Zhou, D., Samovski, D., Okunade, A. L., Stahl, P. D., Abumrad, N. A., Su, X.. CD36 level and trafficking are determinants of lipolysis in adipocytes.